The Distinction of Impulse Buying Behavior in Traditional Markets - S. Hardjati, W. Handayani, E. Iryanti, M. Safeyah, (Opción, 2019)
This study analyzed the differences in the behavior of traditional market consumers in Surabaya and Malang. In this study, 205 respondents from the Surabaya traditional market and 177 respondents from the Malang traditional market were involved. The data were analyzed by t-test to find out if there were significant differences or no differences. From the test results, it shows that the variables of facilities, environment, price, and regret there have no significant differences in respondents in Surabaya and Malang. In conclusion, there are differences in the factors that influence impulse buying behavior in traditional markets in Surabaya and Malang.